Evaluation of the Predictive Value of Myometrial to Endometrial Ratio in Type II Endometrial Cancer: A Case Series [16J]. Issue 1 (May 2017) - Ahmed, Rimsha; Estes, Stephanie; Paroder, Viktoriya; Frimer, Marina; Kesterson, Joshua; Phaeton, Rebecca
Abstract : INTRODUCTION: Endometrial cancer is the most common gynecologic malignancy in the U.S., classified by two histologic subtypes. Type II endometrial cancers are known to be non-estrogen dependent, poorly-differentiated, and with worse prognosis. Diagnostic imaging includes the use of transvaginal ultrasound (TVUS). Current guidelines don't require further endometrial sampling if ultrasonography depicts an endometrial thickness of less than 4 mm. However, ultrasound alone could miss 4% of cancer diagnoses, since it often doesn't correlate with histologic subtypes. This study aims to assess the ratio of myometrial to endometrial thickness obtained via TVUS in Type II endometrial cancer. METHODS: A chart review was performed at two academic centers, to identify all cases of Type II endometrial cancer from January 2009 to December 2014. Using pre-operative TVUS images, four distinct myometrial measurements were made in the longitudinal axis. The measurements were averaged and compared to thickness of the endometrium. Patients were excluded if myometrial or intracavitary lesions were noted. RESULTS: Out of a total of 103 cases of Type II endometrial cancer, 30 met inclusion criteria. Mean myometrial thickness ranged from 7.75 mm to 21.25 mm and endometrial thickness ranged from 2.4 mm to 37 mm. Thickness ratio of myometrium to endometrium ranged from 0.35 to 7.21, with an average ratio of 1.45. CONCLUSION: Type II histologic subtype of endometrial cancer presents with varying thicknesses of the uterine layers noted on TVUS. Significant variations in sonographic characteristics may result in delayed diagnoses compared to Type I endometrial cancers. Further research will be focused on directly comparing both histologic subtypes of endometrial cancer.